2019
DOI: 10.4314/gjpas.v25i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of some oil based muds used in reservoirs in the Niger Delta, Nigeria

Abstract: Rheological properties of some oil based muds used in oil reservoirs located in the Niger Delta area of Nigeria were analyzed using standard methods (American standard for testing and material. Rheological parameters were obtained with a rotational viscometer by relating the shear stress of the fluid to the shear rate of the equipment. Results obtained from two of the oil based muds labelled OBM 3 and OBM 2 ; 1st gel strength (8 -9 lb/ft 2 ), 2nd gel strength (21 -28 IbIft 2 ), plastic viscosity (19-23 cP), yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The ability of the drilling mud to suspend drilling cuttings and other solid additives when there is no applied shear stress is known as the gel strength (Salem et al, 2023). It is a measure of the shear stress required to initiate flow after a static period or a period of inactivity (Onojake and Chikwe, 2019). A higher gel strength value is required to prevent mud sagging and fluid loss, and also to maintain wellbore stability when drilling operations are paused provided it falls within the API range of 2 -35 lb/100ft 2 for 10 minutes gel strength (Biwott et al, 2019;Khan et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of the drilling mud to suspend drilling cuttings and other solid additives when there is no applied shear stress is known as the gel strength (Salem et al, 2023). It is a measure of the shear stress required to initiate flow after a static period or a period of inactivity (Onojake and Chikwe, 2019). A higher gel strength value is required to prevent mud sagging and fluid loss, and also to maintain wellbore stability when drilling operations are paused provided it falls within the API range of 2 -35 lb/100ft 2 for 10 minutes gel strength (Biwott et al, 2019;Khan et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The apparent viscosity (AV) of drilling mud plays a crucial role in suspending drilled cuttings and ensuring effective hole cleaning [20,21]. The AV in Fig.…”
Section: Apparent Viscositymentioning
confidence: 99%
“…Modern Engineering Materials and Efficient Technologies rate is too high, the mud does not lift rock chips from the bottom of the drill, resulting in deposition and can hamper the drilling process [15]. From the test of drilling mud viscosity results with variations of CMC and constant SA concentration, it was found that the CMC addition of 1 g gives the viscosity in the minimum limit of the API 13A (30 cP).…”
Section: Figmentioning
confidence: 99%